If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -9y = 0 Combine like terms: 3y + -9y = -6y -6y = 0 Solving -6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-6'. y = 0 Simplifying y = 0
| 1-16cos^2x=0 | | (X+5)+x=55 | | 13+2x=-39+12x | | -7(2t+7)=-35 | | x^3+4x^2=100*100*100 | | 6x-7+3x+5x-2=8 | | 5y-6=y-3+y | | -(c-10)=-118 | | 2x+25=4x-85 | | (3r+2)=0 | | 4+5=-8+x | | w-2y=7 | | 9-24=39 | | 3(2cos^2(x)-1)= | | 6w-10=2w+4 | | 3n+4=n+5*2 | | 5x+x=55 | | X+.0675X=300 | | 5y-3x-y+2x= | | k=(9s-5t)/4t | | 8*x-(1000/(x^2))=0 | | (-3u-7)(2u+7)=0 | | a/10-8=2 | | 5x+y=73 | | a/10-8= | | (12a^2-23ab-6b)+(4a^2-b^2)+(3a^2+2ab+b^2)= | | ln(z-i)=0 | | 0,42=25/x | | 5a-32=48 | | (5r-30)=0 | | -30/5r | | 9x+5=17+x |